Classification of a subclass of low-dimensional complex filiform Leibniz algebras. - Rakhimov, Isamiddin S.; Said Husain, Sharifah Kartini (Taylor & Francis, 2011)
We give a complete classification of a subclass of complex filiform Leibniz algebras obtained from naturally graded non-Lie filiform Leibniz algebras. The isomorphism criteria in terms of invariant functions are given.